2011
DOI: 10.1029/2010jg001461
|View full text |Cite
|
Sign up to set email alerts
|

Ecological information and water mass properties in the Mediterranean recorded by stable isotope ratios inPinna nobilisshells

Abstract: 18 O values than the specimen from 30 m, likely reflecting differences in salinity. The specimens from 30 m recorded d13 C values less positive than the specimens from 16 m, which we interpreted as an ontogenetic effect observed in previous studies. Estimated calcification temperatures were offset relative to measured water temperature by ∼6.1°C (∼1.4‰). This finding is evident in earlier proxy studies of P. nobilis, although it was not discussed in those studies. Using the seasonal pattern of d 18 O and d 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Results of this study as well as earlier works conducted on the shell chemistry of P. nobilis (e.g., Richardson et al, 1999Richardson et al, , 2004García-March et al, 2011;Gilbert et al, 2017), clearly indicate the great potential of P. nobilis as well as related taxa for sclerochronological research. Over the past decade, research on shell chemistry has been conducted on several species of Pinnidae including Atrina fragilis (Valentine et al, 2011), Atrina rigida (Gilbert et al, 2017), and Pinna carnea (Gilbert et al, 2017).…”
Section: Pinnindae and Shell Chemistrysupporting
confidence: 79%
See 1 more Smart Citation
“…Results of this study as well as earlier works conducted on the shell chemistry of P. nobilis (e.g., Richardson et al, 1999Richardson et al, , 2004García-March et al, 2011;Gilbert et al, 2017), clearly indicate the great potential of P. nobilis as well as related taxa for sclerochronological research. Over the past decade, research on shell chemistry has been conducted on several species of Pinnidae including Atrina fragilis (Valentine et al, 2011), Atrina rigida (Gilbert et al, 2017), and Pinna carnea (Gilbert et al, 2017).…”
Section: Pinnindae and Shell Chemistrysupporting
confidence: 79%
“…Previous studies on the chemical properties of P. nobilis shells include research on oxygen (δ 18 O shell ) and carbon (δ 13 C shell ) stable isotopes (Richardson et al, 1999(Richardson et al, , 2004Kennedy et al, 2001a;Freitas et al, 2005;García-March et al, 2011), as well as element ratios including Mg/Ca and Sr/Ca (Richardson et al, 2004;Freitas et al, 2005). García-March et al (2011) suggested that P. nobilis can be used to reconstruct environmental, ecological and climate changes in the Mediterranean Sea. Following previous analyses of δ 18 O and δ 13 C in P. nobilis shells, the present study focuses on δ 15 N CBOM values of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mollusk shells contain up to 5% organic matter in and between the carbonate crystals (Marin and Luquet, 2004;Rueda and Smaal, 2004). Although there have been a few reports of mollusks precipi tating carbonate out of O-isotope equilibrium (based on the aforementioned equations) (Fastovsky et al, 1993;Fenger et al, 2007;Thébault et al, 2007;Ford et al, 2010;Furguson et al, 2011;García-March et al, 2011), it does seem that most bivalves precipitate near thermodynamic equilibrium (see Wefer and Berger, 1991;Dettman et al, 1999;Kennedy et al, 2001;Lécuyer et al, 2004;Chauvaud et al, 2005;Kim et al, 2007;Wanamaker et al, 2007; and many more), and the empirical paleo-temperature equations based on mollusks have been used with much success. Isotopes of C, N, S, and H in shell organic matter can be relatively easily analyzed.…”
Section: High-resolution Stable Isotope Records: Biological Archives mentioning
confidence: 99%
“…In a recent study, Crippa et al (2016) performed stable isotope analysis of fossil shells of several bivalve species from the lower Pleistocene Arda river marine succession (northern Italy). To the best of our knowledge, the only studies on the potential of stable-isotope ratios in recent bivalve shells in the Mediterranean for paleoclimate reconstruction are that of Maier and Titschack (2010) on Spondylus gaederopus and García-March et al (2011) on Pinna nobilis.…”
Section: Introductionmentioning
confidence: 99%